Antimycobacterial activity of nitrogen heterocycles derivatives: 7-(pyridine-4-yl)-indolizine derivatives. Part VII8-12 - Anda-Mihaela Olaru; Violeta Vasilache; Ramona Danac; Ionel I. Mangalagiu (Taylor & Francis Group, 2017)
A series of 13 compounds having a monoindolizine mono-salt skeleton was designed and synthesised in order to evaluate their antimycobacterial activity. The synthesis is efficient, involving only three steps: two alkylations and one 3 + 2 dipolar cycloaddition. The antimicrobial activity against Mycobacterium tuberculosis H37Rv grown under aerobic conditions was evaluated, eight compounds showing a very good antimycobacterial activity. SAR correlation reveals a certain influence of the R substituent from the para position of benzoyl moiety at position 3 of indolizine. The most active five compounds passed the second stage of anti-TB testing, the assay demonstrating that they are potent against both replicating and non-replicating Mtb, have a bactericidal mechanism of action, are active against drug-resistant Mtb strains, present a moderate to good activity against nontuberculous mycobacteria, a good intracellular activity, and a moderate to high cytotoxicity. For one compound showing a promising anti-TB profile, a complete ADMET study has been performed.